Underwater acoustic communication physical layer key generation scheme - Jingmei LIU; Zhiwei SHEN; Qingqing HAN; Jingwei LIU (Tongxin xuebao)
To ensure the communication safety of unmanned underwater vehicle,a physical layer key generation scheme of underwater acoustic channel based on orthogonal frequency division multiplexing (OFDM) system was proposed.First,a local pilot assistance channel sounding protocol was proposed to solve the reciprocity impaired caused by the great propagation delay in the underwater acoustic channel,ensure high key randomness and enhance the defenses against nearby eavesdroppers.Secondly,double-layer compensation centralized combined with adaptive guard interval quantization method was proposed to improve key agreement rate and key generation rate.Simulation results show that the scheme effectively overcomes the problems of impaired reciprocity and ensures high key generation rate and high randomness on the premise that the key agreement is superior to the existing schemes.